Divergent sex-specific effects on a ketogenic diet: Male, but not female, mice exhibit oxidative stress and cellular senescence - Sung-Jen Wei; Joseph Schell; Wei Qian; Martin Silguero; Agne Baseviciene; Wan Hsi Chen; Rolando Trevino, Jr.; E. Sandra Chocron; Meredith M. Ogle; Mahboubeh Varmazyad; Gloria M. Martinez; Diego Cruz; et al. (Cell Reports, 2025)
Summary: While a ketogenic diet (KD) can improve certain health parameters, evidence from murine and clinical studies suggests that these effects may be dependent on multiple variables. One understudied variable is the role of sex in the response to a KD. Here, we show that a KD-induced increase in p53, p21, and cellular senescence is only observed in male mice, except when they are given estrogen, and in female mice administered tamoxifen. Male, but not female, mice on a KD exhibit an increase in markers of oxidative stress and acetylation of mitochondrial proteins, including manganese superoxide dismutase (MnSOD). Notably, the increases in p53, p21, cellular senescence, MnSOD acetylation, and oxidative stress in male mice on a KD were all prevented by estrogen treatment. In addition, several established antioxidants and an MnSOD chemical mimetic also prevented KD-induced cellular senescence. These results suggest sex specificity in the effects of a KD, with important clinical implications.